Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Having $px^3+(p-3)x^2+(2-p)x=0$ how to find p that this equality have at least 1 positive root ? How can we solve this and similiar things? Because i'm stuck... i did it for quaratic, but i can't solve it.

Any help will be appreciated.

P.S this is not homework, but it was long time ago, now i feel stupid and decided to revise it.

share|improve this question
    
In your case, you can factor by $x$ and find a quadratic. –  Joel Cohen Nov 4 '11 at 12:03
add comment

3 Answers 3

up vote 1 down vote accepted

Firstly, $px^3+(p-3)x^2+(2-p)x=x[px^2+(p-3)x+(2-p)]$. Solution $x=0$ is not a positive root and can, therefore, be safely discarded. We are left with a quadratic in x. This quadratic can only have real solutions when its discriminant $D(p)=(p-3)^2-4p(2-p)=(p-1)(5p-9)$ is non-negative, hence $$ \mbox{either}\quad p\le1 \quad\mbox{or}\quad p\ge 9/5.\qquad (1) $$ The quadratic has two solutions $$ x_{1,2}=\frac{3}{2p}-\frac{1}{2}\pm\frac{1}{2p}\sqrt{(p-1)(5p-9)}.\qquad (2_{1,2}) $$ For $p>0$ solution ($2_1$) is the greater of two. When $p=9/5$, ($2_1$) gives $x=1/3>0$, and since $D(p)$ is an increasing function for $p\ge 9/5$, we conclude that $p\ge 9/5$ would satisfy the problem requirements.

The case when $p\le1$ is a bit more complicated. There are several cases to consider.

  1. When $0<p\le 1$, solution ($2_1$) gives $x=1>0$, and since $\sqrt{D(p)}/p$ is an increasing function for $0<p\le 1$, we conclude that $0<p\le 1$ satisfies the problem requirements.
  2. Solution (2) is invalid when $p=0$. Direct substitution of $p=0$ into the original equation gives $x=2/3$, hence, $p=0$ satisfies the problem requirements (the same result can be obtain by taking a limit of ($2_2$) as $p\to +0$).
  3. When $p<0$, solution ($2_2$) is the greater of two. Analysing whether it is positive directly is a bit difficult. Instead, we can do a simpler argument, similar to pharmine's. We know about the constant term of the quadratic that $(2-p)/p=x_1x_2$. When $p<0$ this term is always negative. Overall, (1) says that quadratic has two roots and $(2-p)/p=x_1x_2<0$ says that these roots are of the opposite sign, hence, one of them will always be positive.

We can now combine these observations into a full answer. Given equation has at least one positive solution provided $$ p\le 1 \quad\mbox{or}\quad p\ge 9/5. $$

share|improve this answer
    
Seems like a good solution, but i can't find p for which this equation has none positive roots, i tried something like $p=-0.15$ wolframalpha.com/input/… –  Chris Nov 4 '11 at 13:34
    
(2) has a typo: $\frac{1}{2p}\sqrt{\cdots}$, not $\frac12\sqrt{\cdots}$ –  pharmine Nov 4 '11 at 13:48
    
@Chris: Sorry, I made a typo while copying the quadratic and solved wrong (harder) problem. Will fix in a moment. –  Aleksey Pichugin Nov 4 '11 at 14:36
    
@pharmine: Sorry, made a typo. Will fix now. –  Aleksey Pichugin Nov 4 '11 at 14:37
    
Thanks, everything's clear now :) –  Chris Nov 4 '11 at 15:06
add comment

Following Aleksey Pichugin's argument, the question is to find the condition in which $px^2+(p-3)x+(2-p)=0$ ($\ast$) has at least one positive root.

First, its discriminant must be non-negative: $(p-3)^2-4p(2-p)=(p-1)(5p-9)\ge 0$, which means $p\le 1$ or $p\ge 9/5$. (1)

Provided (1) is satisfied, the negation of 'the equation ($\ast$) has at least one positive root' is 'the equation ($\ast$) has two nonpositive (=negative or zero) roots'. Let's consider the latter condition, which seems a bit easier.

If $p=0$, ($\ast$) reduces to $-3x+2=0$ and it has a positive root; we assume $p\ne 0$ below. Let the two roots of the equation be $\alpha$ and $\beta$ (provided (1) is satisfied). Then '$\alpha\le 0$ and $\beta\le 0$' is equivalent to '$\alpha\beta\ge 0$ and $\alpha+\beta\le 0$'. Here $\alpha\beta=\frac{2-p}{p}$, while $\alpha+\beta=-\frac{p-3}{p}$, so this means '$p(2-p)\ge 0$ and $p(3-p)\le 0$'. There are no $p\ne 0$ satisfying both inequalities.

Therefore the condition we want to have is (1), which is '$p\le 1$ or $p\ge 9/5$'.

share|improve this answer
add comment

$px^3+(p-3)x^2+(2-p)x=x(px^2+(p-3)x+(2-p))=0\Rightarrow$

$\Rightarrow x_1=0$ and: $$x_{2,3}=\frac{3-p \pm \sqrt {5p^2-14p+9}}{2p}$$ so you have that:

$$\frac{3-p - \sqrt {5p^2-14p+9}}{2p}>0 \lor \frac{3-p + \sqrt {5p^2-14p+9}}{2p}>0$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.